Estimating the Additive Benefit of Surgical Excision to Stereotactic Radiosurgery in the Management of Metastatic Brain Disease. Issue 6 (June 2015) - Quigley, Matthew R.; Bello, Nicholas; Jho, Diana; Fuhrer, Russell; Karlovits, Stephen; Buchinsky, Farrel J.
Abstract : BACKGROUND: There are limited data on the benefits of surgical tumor resection plus stereotactic radiosurgery (SRS) in comparison with SRS alone for patients with oligometastatic brain disease. OBJECTIVE: To determine the benefit of adding resection to SRS. METHODS: We reviewed 162 consecutive patients with oligometastatic brain disease, who underwent surgical tumor resection and SRS boost (n = 49) or SRS alone (n = 113). Patients receiving prior whole brain radiation therapy were excluded. Factors related to patient survival and time-to-local recurrence (TTLR) were determined by Cox regression. The effect of complete resection + SRS boost on survival was further explored by propensity score matching. RESULTS: The average age of the cohort was 65.3 years, it was 49.4% female, and included 260 brain tumors, of which 119 tumors were single. Seventy-three brain tumors recurred (28%). TTLR was related to radiation-sensitive pathology (hazards ratio [HR] = 0.34, P = .001), treatment volume (HR = 1.078/mL, P = .002), and complete tumor resection (HR = 0.37, P = .015). Factors related to survival were age (HR = 1.21/decade, P = .037), Eastern Cooperative Oncology Group performance score (HR = 1.9, P = .001), and complete surgical resection (HR = 0.55, P = .01). Propensity score matched analysis of complete surgical resection + SRS boost (n = 40) vs SRS alone (n = 80) yielded nearly identical survival results (HR = 0.52, P = .030) compared with the initial unmatched sample. Incomplete tumor resection had both median survival and TTLR equivalent to SRS alone. CONCLUSION: Complete surgical resection + SRS boost is associated with improved survival and reduced likelihood of local tumor recurrence in comparison with SRS alone. Incomplete resection did not improve survival or TTLR compared with SRS alone. ABBREVIATIONS: ECOG, Eastern Cooperative Oncology Group HR, hazards ratio RPA, recursive participating analysis SRS, stereotactic radiosurgery WBXRT, whole brain radiation therapy Abstract : Supplemental Digital Content is Available in the Text.